THE IMPACT OF CHILDHOOD FAMILY EXPERIENCE ON PARTNERSHIP PROBLEMS AND BIRTH-RATE IN ADULTHOOD - Tretjakova, Indra; Pipere, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The causes for the partnership problems and low birth-rate can be looked upon not only through an economical discourse, but also via the thorough exploration of psychological determinants of sustainable family relationships. The skills and abilities for the development of such relationships significantly depend on the characteristics of childhood family experience. Exploring the factors that influence partnership quality and birth-rate in Latvia 221 respondents were surveyed (185 women and 36 men) aged from 20 to 40. Majority of the sample indicated to their negative childhood experience (mostly parents’ conflicts, divorce, neglect, alcohol abuse) and admitted an impact of this experience on their partnership in adulthood. The respondents with negative childhood family experience reported conflicts in their current relationships more often than their counterparts with supportive childhood experience. The most frequent partnership problems appeared to be emotional violence and computer addiction, at much less rate – alcohol abuse. Though, the statistically significant correlations between the childhood family experience and the partnership problems as well as between the childhood family experience and nymber of childen in family were not found in the given sample. The problem of drug addiction had a statistically significant negative correlation with the number of children in family. Future research could focus on the ways in which positive and adverse childhood experiences interact to influence partnership quality and birth-rate.